Papilla with Separate Bile and Pancreatic Duct Orifices - Rana, Surinder Singh; Bhasin, Deepak Kumar (JOP. Journal of the Pancreas, 2013)
No abstract avilable. Image: Papilla with separate bile duct and pancreatic duct orifice.